UNFSS AT5 HDP COALITION: Meetings Summary - CGIAR FOCUS Climate Security (CGIAR System Organization, 2022)
In its Phase 1 (September to December 2022) the Climate, Security, and Food Systems theme workstream of the HDP coalition worked together with its members to collate state-of-the-art evidence on the connection between climate, food, and peace and security. Over the course of 5 meetings, various coalition members presented state-of-the-art evidence on the connection between climate, food, and peace and security.